Internet use and subsequent health and well-being in older adults: An outcome-wide analysis. (May 2022) - Nakagomi, Atsushi; Shiba, Koichiro; Kawachi, Ichiro; Ide, Kazushige; Nagamine, Yuiko; Kondo, Naoki; Hanazato, Masamichi; Kondo, Katsunori
Abstract: There is a growing, but inconclusive, evidence on the beneficial influence of the Internet on the health/well-being of older people. This study aims to examine outcomes-wide associations between frequency of internet use and subsequent health/well-being among older individuals. We used the three-wave data (2013, 2016, and 2019) from the Japan Gerontological Evaluation Study. Our exposure was frequency of internet use (not at all/use a few times a month/use a few times a week/use almost every day) in 2016. We assessed 34 health/well-being outcomes in 2019 across six dimensions. Pre-exposure characteristics and prior outcome levels in 2013 were adjusted. We included 5879 respondents for 4 outcomes (death, dementia, and functional disability) and 4232 respondents for 30 other outcomes. Using the Internet almost every day (vs. not using at all) in 2016 was associated with some outcomes in 2019 in three dimensions: physical/cognitive health (better instrumental activities of daily living), social well-being (more frequent participation in sports groups, meeting friends more frequently, and seeing more friends within a month), and health behaviors (receiving health screening) (p < 0.05 for these associations after Bonferroni correction). It was not associated with any outcomes of three other dimensions: psychological distress, subjective well-being, or pro-social/altruistic behaviors. Highlights: We examine outcomes-wide associations between frequency of internet use and subsequent health/well-being among older people. This is one of the first studies to investigate these relationships by leveraging the three-wave structure of the data. Internet use was associated with some outcomes of physical/cognitive health, social well-being, and health behaviors. It was associated with no outcome of psychological distress, subjective well-being, or pro-social/altruistic behaviors.